2010
DOI: 10.1095/biolreprod.109.083154
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 Is Essential for Mouse Endometrial Gland Development and Fertility1

Abstract: During embryonic development, Foxa2 is required for the formation of the node and notochord, and ablation of this gene results in defects in gastrulation, neural tube patterning, and gut morphogenesis. Foxa2 has been shown to be expressed specifically in the glandular epithelium of the murine uterus. To study the uterine function of Foxa2, this gene was conditionally ablated in the mouse uterus by crossing mice with floxed Foxa2 alleles, Foxa2(loxP/loxP), with the Pgr(cre) mouse model. Pgr(cre/+) Foxa2(loxP/lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 51 publications
7
110
1
Order By: Relevance
“…Forkhead box A2 (Foxa2) is expressed specifically in the uterine glandular epithelium (Besnard et al, 2004). Uterine-specific ablation of this gene in mice results in defective uterine gland formation and dysfunctional uterine stroma unable to support embryo invasion and decidualization (Bazer, 2010; Jeong et al, 2010). Notably, LIF expression is significantly decreased in Foxa2 deficient uteri, whereas administration of recombinant LIF can partially restore decidualization in null females (Bazer, 2010; Jeong et al, 2010), suggesting that Foxa2 may be required for normal glandular LIF expression.…”
Section: Cell-cell Interactions: the Nature Of Embryo Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Forkhead box A2 (Foxa2) is expressed specifically in the uterine glandular epithelium (Besnard et al, 2004). Uterine-specific ablation of this gene in mice results in defective uterine gland formation and dysfunctional uterine stroma unable to support embryo invasion and decidualization (Bazer, 2010; Jeong et al, 2010). Notably, LIF expression is significantly decreased in Foxa2 deficient uteri, whereas administration of recombinant LIF can partially restore decidualization in null females (Bazer, 2010; Jeong et al, 2010), suggesting that Foxa2 may be required for normal glandular LIF expression.…”
Section: Cell-cell Interactions: the Nature Of Embryo Implantationmentioning
confidence: 99%
“…Uterine-specific ablation of this gene in mice results in defective uterine gland formation and dysfunctional uterine stroma unable to support embryo invasion and decidualization (Bazer, 2010; Jeong et al, 2010). Notably, LIF expression is significantly decreased in Foxa2 deficient uteri, whereas administration of recombinant LIF can partially restore decidualization in null females (Bazer, 2010; Jeong et al, 2010), suggesting that Foxa2 may be required for normal glandular LIF expression. Mice systemically lacking Wnt7a have a stratified luminal epithelium surrounded by a shallow stroma layer devoid of glands, in contrast to the simple columnar structure in the wild-type (Miller and Sassoon, 1998).…”
Section: Cell-cell Interactions: the Nature Of Embryo Implantationmentioning
confidence: 99%
“…Subsequently, LIF was found to be essential for blastocyst implantation in mice, as Lif null mice were infertile due to a failure of blastocyst implantation (Stewart et al ., 1992). Recent studies found that a number of knockout ( lymphoid enhancer factor 1 or Lef1 ) and conditional knockout mice [catenin (cadherin associated protein), beta 1 or Ctnnb1; forkhead box A2 or Foxa2, wingless-related MMTV integration site 4 or Wnt4; and Wnt7a ] lack glands in the adult uterus (Dunlap et al ., 2011, Franco et al ., 2011, Franco et al ., 2010, Jeong et al ., 2010, Jeong et al ., 2009, Shelton et al ., 2012). Many of those mice exhibit defects in blastocyst implantation and uterine decidualization and thus fertility, which can be attributed to the absence of LIF and other uterine gland-derived factors.…”
Section: Uterine Glands and Pregnancy In Micementioning
confidence: 99%
“…Results with the aglandular PUGKO mouse model, along with those from conditional Foxa2 mutant mice that have much reduced uterine glands (Jeong et al ., 2010) and Lif null mice (Stewart et al ., 1992), strongly support that hypothesis.…”
Section: Biological Role Of Uterine Glands and Their Secretions In Immentioning
confidence: 99%
See 1 more Smart Citation